Pengembangan Perilaku Berliterasi Siswa Berbasis Kegiatan Ilmiah: Hasil-hasil Penelitian dan Implementasinya di Sekolah - Suyono Suyono (Universitas Negeri Malang, 2016)
This essay argues that literacy is of paramount importance in schools, be it for the purpose of students' completion of their studies, of their study career, or of their life-long education. To these ends, literacy necessitates serious, systematic, and contextual undertakings. This article will selectively out-line the views of a number of experts and critically review some research findings in the area, which, by and large, advocate the significance of efforts to improve the quality of literacy. The paper will also provide various examples of how literacy might be enhanced, for instance, by administering literacy hour and whole school literacy. An argument that scientific activities can serve as bases for the im-provement of students' literacy will conclude the essay.